Implementasi Metode Belajar Diferensiasi dalam Pembelajaran Fiqh di MTsN Lubuk Buaya - Adisty, Rahma Indah; Wiza, Rahmi (ALSYS, 2025)
This study investigates the implementation of differentiated learning methods in Fiqh education at MTsN Lubuk Buaya, aiming to accommodate the diverse learning styles of students. It recognizes that students possess varying preferences, categorized as visual, auditory, and kinesthetic. The primary objective of this research is to enhance student engagement and understanding by employing tailored teaching strategies that align with these preferences. A qualitative approach was adopted, utilizing observations, interviews, and document analysis to gather comprehensive data. The findings indicate that differentiated instruction significantly enhances student motivation and comprehension levels. However, the study also identifies challenges, including administrative burdens and limitations in classroom space, which can hinder effective implementation. Ultimately, the research concludes that effective differentiation not only improves learning outcomes but also fosters a more inclusive and engaging educational environment, ensuring that all students can thrive in their learning experiences.